Hijacking Dlg1 for Oncogenic Phosphatidylinositol 3-Kinase Activation in Human Epithelial Cells Is a Conserved Mechanism of Human Adenovirus E4-ORF1 Proteins - Kumar, Manish (J Virol, 2014)
The E4-ORF1 gene of human adenoviruses encodes a 14-kDa protein that promotes viral replication as well as cellular metabolic reprogramming, survival, and transformation by constitutively activating cellular phosphatidylinositol 3-kinase (PI3K). We recently reported that the E4-ORF1 protein from subgroup D human adenovirus type 9 upregulates and oncogenically activates PI3K by a novel mechanism involving separate interactions of E4-ORF1 with cellular discs large 1 (Dlg1) and PI3K to form a ternary complex that translocates to the plasma membrane (K. Kong, M. Kumar, M. Taruishi, and R. T. Javier, PLoS Pathog. 10:e1004102, 2014, doi:10.1371/journal.ppat.1004102). The current study was carried out to investigate whether other human adenovirus E4-ORF1 proteins share this mechanism of action. The results showed that in human MCF10A epithelial cells, stable expression of E4-ORF1 proteins encoded by representative human adenovirus serotypes from subgroups A to D induce ternary complex formation, Dlg1-dependent PI3K activation, PI3K protein elevation, Dlg1 and PI3K membrane recruitment, and PI3K-dependent cellular transformation. The first three of these E4-ORF1 activities were also observed in MCF10A cells infected with each wild-type human adenovirus from subgroups A to D. Our findings indicate that most, if not all, human adenovirus E4-ORF1 proteins share a conserved molecular mechanism of PI3K activation, which confers a common capacity to promote oncogenic transformation in human epithelial cells. IMPORTANCE PI3K activation by the adenovirus E4-ORF1 protein mediates oncogenic cellular transformation by human adenovirus type 9, augments viral protein expression and replication by human adenovirus type 5, and dysregulates cellular glucose and lipid metabolism by human adenovirus type 36. For the first time, we report that E4-ORF1 proteins from human adenoviruses in subgroups A to D evolved a conserved molecular mechanism to mediate constitutive PI3K activation that can provoke oncogenic transformation in human epithelial cells. The results raise potential safety concerns about the use of vectors encoding the E4-ORF1 gene in human gene therapy and vaccination. Our findings further suggest that the conserved mechanism revealed here may be targeted for development of therapeutic drugs to treat and prevent adenovirus-associated human diseases.